2020
DOI: 10.4102/sajhivmed.v21i1.1152
|View full text |Cite|
|
Sign up to set email alerts
|

Southern African guidelines on the safe, easy and effective use of pre-exposure prophylaxis: 2020

Abstract: No abstract  available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…This study evaluated the benefits of tenofovir-silver nanoparticles conjugate on the ultrastructural and cytoarchitectonic properties of the prefrontal cortex in type-2 diabetic rats. Tenofovir disoproxil fumarate (TDF) is commonly used for pre-exposure prophylaxis alone or in combination with other antiretroviral drugs as post-exposure prophylaxis [46,47]. Despite TDF's low CNS-penetration rate, studies have reported its neurotoxic effect and diabetic and neurocognitive implications [11,12,19].…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated the benefits of tenofovir-silver nanoparticles conjugate on the ultrastructural and cytoarchitectonic properties of the prefrontal cortex in type-2 diabetic rats. Tenofovir disoproxil fumarate (TDF) is commonly used for pre-exposure prophylaxis alone or in combination with other antiretroviral drugs as post-exposure prophylaxis [46,47]. Despite TDF's low CNS-penetration rate, studies have reported its neurotoxic effect and diabetic and neurocognitive implications [11,12,19].…”
Section: Discussionmentioning
confidence: 99%
“…[6]; (4) pregnancy testing is at no cost in our DoH scenarios since it occurs through the family planning department and only done at initiation; and (5) required tests as per DoH guidelines (Figure 1). We excluded creatinine testing in our DoH and scaled‐DoH scenario analysis since it is not essential for AGYW [21]. A detailed description of items included in each costing category is in Table 1 and Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…† Creatinine test is recommended at PrEP initiation but not essential in well individuals under the age of 40. It should, however, be performed at PrEP initiation and repeated at months 6 and 12 in clients with co‐morbidities, above 40 years, pregnant women or on concomitant medication [21]. ‡ HIV serology test is required at initiation and at least every 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…75 As such, all TGD clients should be offered pre-exposure prophylaxis (PrEP). 76 PrEP has no impact on the concentration of oestradiol or testosterone levels and can be safely prescribed in a client on HT. 77 HIV testing and counselling services should address TGD-specific needs, and options, such as HIV self-screening, index testing and partner notification, should be offered.…”
Section: Hivmentioning
confidence: 99%